Endometrial Disease in Six Cats with Clinical and Histopathological Features Resembling Atypical Endometrial Hyperplasia in Humans. (November 2021) - Suzuki, Satoshi; Kitamura, Hidetomo; Hayashi, Kohtaro; Nakashima, Tomomi; Okamura, Masaru; Shirai, Katsuaki; Kariya, Takuro
Summary: In humans, atypical endometrial hyperplasia (AEH) is considered as a precancerous lesion of endometrial adenocarcinoma (EA), from which it must be distinguished. Precancerous lesions have not been reported in cats with EA. We now document the histopathological features of endometrial lesions in six cats, which histopathologically resembled human AEH and had a good prognosis following ovariohysterectomy. Grossly, one cat presented with papillomatous nodules and three cats had pyometra. Histopathologically, proliferation of endometrial epithelial cells without atypia was observed in all cases. In some regions of the endometrium, cells had increased atypia and were arranged in stratified layers, which formed irregular ducts and papillary structures. No invasive behaviour or vascular invasion was observed. On the basis of these findings, the cats were diagnosed with non-invasive or early-stage adenocarcinoma. Immunohistochemistry for oestrogen receptor and progesterone receptor revealed an inverse correlation with the severity of the endometrial lesions and degree of malignancy of tumour cells. Ki67 labelling revealed that mitotic activity increased as the lesion developed. All cats survived, with a median survival time of 385 days (range: 229–744 days). The distribution of the histopathological endometrial changes and the non-invasive behaviour in these feline cases resemble cases of AEH in humans.